2002
DOI: 10.1006/icar.2002.6834
|View full text |Cite
|
Sign up to set email alerts
|

The Permanent and Inductive Magnetic Moments of Ganymede

Abstract: Data acquiredby the Galileo magnetometer on five passes by Ganymede have been used to characterize Ganymede's internal magnetic moments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
418
2
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(481 citation statements)
references
References 27 publications
18
418
2
5
Order By: Relevance
“…All models are composed of an ice shell including a subsurface ocean and a rocky mantle. Oceans are predicted for all three satellites (Kivelson et al 1999(Kivelson et al , 2000(Kivelson et al , 2002Khurana 1998;Papalardo et al 1999) and theoretical models shows that internal oceans are conceivable for Europa, Ganymede and for a partly differentiated Callisto with thicknesses as large as few hundred km (Schubert et al 2004). The Europa ocean is likely situated above the rocky mantle.…”
Section: Interior Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…All models are composed of an ice shell including a subsurface ocean and a rocky mantle. Oceans are predicted for all three satellites (Kivelson et al 1999(Kivelson et al , 2000(Kivelson et al , 2002Khurana 1998;Papalardo et al 1999) and theoretical models shows that internal oceans are conceivable for Europa, Ganymede and for a partly differentiated Callisto with thicknesses as large as few hundred km (Schubert et al 2004). The Europa ocean is likely situated above the rocky mantle.…”
Section: Interior Modelsmentioning
confidence: 99%
“…The presence of an ocean for the Galilean satellites is inferred from analysis of the geological structures at the surface of the satellites and magnetic measurements (Kivelson et al 1999(Kivelson et al , 2000(Kivelson et al , 2002Khurana 1998;Papalardo et al 1999). Van Hoolst et al (2008, 2009) and Baland & Van Hoolst (2010) have investigated the librational response of the Galilean satellites and Titan in the presence of a subsurface ocean and showed that it increases the librational amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Galileo magnetic field measurements have found indications of subsurface oceans on Europa (Khurana et al 1998;Kivelson et al 1999), Ganymede (Kivelson et al 2002) and Callisto (Khurana et al 1998;Kivelson et al 1999) where endogenic chemistry is likely to have influenced the composition of these internal oceans. The extensive resurfacing of Europa and Ganymede suggest exchange between an interior ocean and the surface.…”
Section: The Galilean Satellitesmentioning
confidence: 99%
“…Some satellites even possess their own magnetic field which interacts with the parent's one [e.g., Europa has an induced magnetic field (Kivelson et al 2000), Ganymede has an intrinsic magnetic field (Kivelson et al 2002)]. …”
Section: Magnetospherementioning
confidence: 99%